Kinship, Adscription and Child Rearing. Cultural Constructions of International Adoption and Circulation of Children - Grau Rebollo, Jorge (Revista de Antropología Social, 2011)
The relevance of children adscription has clearly suggested the need of taking into account the various forms of circulation of children considered as a global phenomenon of particular significance in the replacement strategies of a given group, as well as for its social cohesion. Confined for a long time to the label of “fictive kinship”, some of the specific forms of this movement, such as international adoption, emerged in the theoretical arena as movements of children under international law blossomed and multi-faceted debates over their economic, ethical and political corollaries developed both in academic and professional forums and in mass media. In this article I address some of the most fruitful lines in the recent study of circulation of children and international adoption practices, both regarded as phenomena of global dimensions. I try to do this by emphasizing the need of paying special attention to cultural constructions of adscription processes and child rearing.
Keywords: International adoption; circulation of children; anthropology of kinship; child rearing; folk concepts; ethnography; transcultural comparison